Boosting hot electrons in hetero-superstructures for plasmon-enhanced catalysis - Guo, Jun (2018)
Hetero-nanostructures featured with both strong plasmon absorption and high catalytic activity are believed to be ideal platforms to realize efficient light-driven catalysis. However, in reality, it remains a great challenge to acquire high-performance catalysis in such hetero-nanostructures due to poor generation and transfer of plamson-induced hot electrons. In this report, we demonstrate that Au nanorod@Pd superstructures (Au@Pd SSs), where the ordered Pd nanoarrays are precisely grown on Au nanorod surfaces via solution-based seed-mediated approach, would be an excellent solution for this challenge. Both experiment and theory disclose that the ordered arrangement of Pd on Au nanorod surfaces largely promotes hot electron generation and transfer via amplified local electromagnetic field and decreased electron–phonon coupling, respectively. Each effect is separately highlighted in experiments by the significant plasmon-enhanced catalytic activity of Au@Pd SSs in two types of important reactions with a distinct time scale of bond-dissociation event: molecular oxygen activation and carbon–carbon coupling reaction. This work opens the door to design and application of new generation photocatalysts.